Організаційні основи аудиту в агропромисловому комплексі України та країнах Європи: порівняльний аналіз - Приходько, Ігор Павлович; Prikhodko, Ihor (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2025)
У статті здійснено порівняльний аналіз організації аудиту в агропромисловому комплексі України та країн Європейського Союзу. Актуальність теми зумовлена необхідністю підвищення прозорості, надійності та ефективності фінансового контролю в аграрному секторі, особливо в умовах євроінтеграційного курсу України. Дослідження показує, що система аудиту в Україні має низку недоліків: фрагментарність нормативного регулювання, слабкий розвиток інституційної інфраструктури, обмежене професійне середовище, а також недостатнє впровадження Міжнародних стандартів аудиту (МСА). Для порівняння, у країнах ЄС організація аудиту базується на чітко визначеній правовій базі, забезпечується високий рівень незалежності аудиторів, діють ефективні механізми публічного нагляду, а також активно впроваджуються цифрові технології в аудиторську практику. Зокрема, обов'язковий аудит охоплює ширший спектр суб'єктів аграрного сектору, застосовуються уніфіковані підходи до оцінки якості аудиторських послуг, а також діє ефективна система ліцензування та професійного розвитку аудиторів. На основі аналізу запропоновано рекомендації щодо вдосконалення вітчизняної моделі аудиту в аграрному секторі, серед яких: посилення державного нагляду за якістю аудиту, розширення сфери обов'язкового аудиту для середніх підприємств, впровадження цифрових інструментів аудиту, а також гармонізація національного законодавства із законодавством ЄС. Результати дослідження мають як теоретичне, так і практичне значення — для науковців, політиків, аудиторів, управлінців та викладачів, які працюють у сфері аграрної економіки та фінансового контролю. This article presents a comparative analysis of audit organization practices in the agro-industrial sectors of Ukraine and the European Union. The relevance of the study stems from the increasing need to ensure transparency, reliability, and efficiency in financial control mechanisms within the agricultural sector, particularly in the context of Ukraine's alignment with European integration standards and the growing demand for accountability in public and corporate governance. The research highlights that the Ukrainian audit system in the agro-industrial complex is characterized by fragmented regulatory provisions, underdeveloped institutional infrastructure, a narrow professional auditing environment, and insufficient harmonization with International Standards on Auditing (ISA). In contrast, the EU audit framework demonstrates a well-established regulatory environment, a high degree of auditor independence, stringent licensing and qualification requirements, and effective integration into a broader European financial supervisory architecture. The study identifies key divergences in several dimensions, including the legal status of audit institutions, audit obligations for agribusiness entities, the consistent application of ISA, the extent of public and independent quality control mechanisms, and the adoption of digital tools and innovative technologies in audit processes. Based on the comparative analysis, the article proposes a set of recommendations aimed at enhancing Ukraine's audit system in the agro-industrial sector. These include: strengthening public oversight of audit quality, promoting continuous professional development for auditors, expanding the scope of mandatory audit for medium-sized agricultural enterprises, implementing digital audit solutions and automated financial analysis tools, and aligning national audit legislation with the EU acquis communautaire. The findings contribute to the development of a transparent, modern, and efficient audit system in Ukraine's agrarian economy, one that supports financial accountability, investor confidence, and international competitiveness. The study holds theoretical value for scholars in the fields of audit, agricultural economics, and public policy, and offers practical implications for policymakers, audit practitioners, academic institutions, and managers in the agribusiness sector.
Оrganizational foundations of audit in the agro-industrial complex of Ukraine and European countries: comparative analysis
Keywords: аудит; audit; агропромисловий комплекс; agro-industrial complex; Європейський Союз; European Union; фінансовий контроль; financial control; міжнародні стандарти аудиту; International Standards on Auditing; аудиторська діяльність; auditing practice; нормативно-правове регулювання; regulatory framework; цифровізація аудиту; audit digitalization; професійна незалежність; professional independence; якість аудиторських послуг; audit quality